2019
DOI: 10.1177/016146811912100503
|View full text |Cite
|
Sign up to set email alerts
|

Can Education Reduce Political Polarization? Fostering Open-Minded Political Engagement during the Legislative Semester

Abstract: Background In the United States, elected leaders and the general public have become more politically polarized during the past several decades, making bipartisan compromise difficult. Political scientists and educational scholars have argued that generating productive political cooperation requires preparing members of democratic societies to productively negotiate their political disagreements. Numerous prior studies on civic learning have focused on fostering youth political engagement, but little research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Based on a set of civic education interventions (school councils, debate teams and mock elections), Keating and Janmaat (2016) show that such activities can indeed have positive and independent medium-term effects on electoral participation, by encouraging political engagement from students even though they have left the confines of the school. Levy et al (2019) provide evidence with their study that participating in an extended discussion-based political simulation (including trial elections) can support various dimensions of high school students' political and electoral engagement. However, Öhrvall and Oskarsson (2020) do not find any effects when examining whether the propensity to vote in elections is higher among pupils from upper-secondary school who have previously experienced a student mock election.…”
Section: Empirical-quantitative Research In Political Didactics On (D...mentioning
confidence: 91%
“…Based on a set of civic education interventions (school councils, debate teams and mock elections), Keating and Janmaat (2016) show that such activities can indeed have positive and independent medium-term effects on electoral participation, by encouraging political engagement from students even though they have left the confines of the school. Levy et al (2019) provide evidence with their study that participating in an extended discussion-based political simulation (including trial elections) can support various dimensions of high school students' political and electoral engagement. However, Öhrvall and Oskarsson (2020) do not find any effects when examining whether the propensity to vote in elections is higher among pupils from upper-secondary school who have previously experienced a student mock election.…”
Section: Empirical-quantitative Research In Political Didactics On (D...mentioning
confidence: 91%
“…Teachers who perceive they have greater instructional agency as well as support from the colleagues and community are more likely to engage media critically and broach controversial issues in their classrooms (Stoddard et al, 2022). Within schools, students who have opportunities to express their opinions in safe, open classroom climates report experiencing greater civic self-efficacy and more quality civic discourse (Barber et al, 2021; Levy et al, 2019). Research has found US administrators (i.e., principals) serve a pivotal role in supporting open classroom dialogue regarding political contentious issues, as supporters or barriers to open discourse (DiGiacomo et al, 2021; Journell, 2022).…”
Section: Conceptual Framingmentioning
confidence: 99%
“…Le, K. et al, based on an examination of exogenous educational differences caused by compulsory education reforms in 39 countries, were informed that education fosters students' political interest and supportive attitudes towards political freedom [12]. Using a combination of quantitative and qualitative methods, Levy, B. L. M. et al examined the development of open political participation (OMPE) among adolescents during their participation in a public high school program and found that students who participated in the program showed great enthusiasm and openness to politics [13]. Marta Koczyńska.…”
Section: Introductionmentioning
confidence: 99%